1988
DOI: 10.2307/3899516
|View full text |Cite
|
Sign up to set email alerts
|

Plant Responses to Pine Management and Deferred-Rotation Grazing in North Florida

Abstract: Responses of herbaceous and woody plants to combinations of 4 pine management and 4 grazing management systems were tested on a wet-flatwoods site in the pintwiregrass vegetation type of north Florida. Frequency of occurrence of herbaceous species and foiii cover of woody species were determined in natural stands of SO-year-old slash and iongleaf pine (Pinus elliottii Engelm. and P. pahstris Mill.) and compared to similar forest sites that were harvested and site prepared by double-chopping and not replanted w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Pennines 27 Titlyanova et al 1988, Sweden: C)Jand limestone grassland/Ve-17.1 18.9 A. Titlyanova, person-ronica-A venula a/ communication NORTH AMERICA 28 Lewis et al 1988 USA: Florida flatwoods/ Pinus-Aristida 28 5.0 32.0 29 Launchbaugh 1955 USA: Texas coastal prairie/Andropo-10.5 28.8 gon-Stipa 30 Brady et al 1989 USA: Arizona Semidesert grassland/ Bou--1.7 32.4 teloua-Eragrostis 30 t Aboveground net primary production (ANPP) or peak standing crop (peak standing crop was most often reported). ANPP of grazed treatments usually based upon harvest within temporary cages that exclude herbivory only during the year of study (see Methods: Response variables for details).…”
Section: Appendixmentioning
confidence: 99%
“…Pennines 27 Titlyanova et al 1988, Sweden: C)Jand limestone grassland/Ve-17.1 18.9 A. Titlyanova, person-ronica-A venula a/ communication NORTH AMERICA 28 Lewis et al 1988 USA: Florida flatwoods/ Pinus-Aristida 28 5.0 32.0 29 Launchbaugh 1955 USA: Texas coastal prairie/Andropo-10.5 28.8 gon-Stipa 30 Brady et al 1989 USA: Arizona Semidesert grassland/ Bou--1.7 32.4 teloua-Eragrostis 30 t Aboveground net primary production (ANPP) or peak standing crop (peak standing crop was most often reported). ANPP of grazed treatments usually based upon harvest within temporary cages that exclude herbivory only during the year of study (see Methods: Response variables for details).…”
Section: Appendixmentioning
confidence: 99%
“…Twenty-eight l-ha test pastures were selected for treatments (Lewis et al 1988). The remaining area was divided into 3 holding units for cattle when they were not grazing the test pastures.…”
Section: Study Site On Species Diversitymentioning
confidence: 99%
“…Using frequency of occurrence as a measure of the abundance of each herbaceous species, we computed species count, Shannon's index, and Simpson's index as 3 commonly employed measures of average species rarity. There were no significant differences due to the deferred-rotation treatments (Lewis et al 1988) so these data were combined. To illustrate the overall results, data from the chopped-only treatment for frequency of occurrence of herbaceous species were used to compare diversity (Fig.…”
Section: Effects On Common Diversity Indicesmentioning
confidence: 99%
“…Increased grass production, decreased herb production, and altered composition were documented in dry flatwood sites under grazing pressure (Duvall and Linnartz 1967). However, Lewis Tanner, and Terry (1988) found that grazing had little effect on occurrence of herbaceous species in pine-wiregrass communities. Intermediate grazing may prevent highly competitive species from excluding others, thus enhancing species richness (reviewed in Walker and Peet 1983).…”
Section: Livestock Grazingmentioning
confidence: 99%